Study of the properties of a hybrid composite thermoplastic matrix/vegetable fillers - BELLILI, Nadira (Biopolymer Applications Journal, 2025)
The study carried out in this work aimed to develop and characterize hybrid composites based on polychloride of vinyl reinforced with date stone flour (DSF) and starch with PVC%/DSF%/ starch % percentages: 80/0/0, 80/20/0, 80/15/5, 80/10/10, 80/5/15 and 80/0/20 respectively. We were particularly interested in the problem of matrix-filler interfacial adhesion due to different characters of the constituent deferens. Several techniques have been used to characterize the composites developed, and the impact of hybridization on the mechanical and physical properties elaborate materials were studied. The incompatibility and poor interfacial adhesion between the different constituents leads to the appearance of phenomenon of embrittlement of the prepared materials, and consequently the reduction in stress, elongation at break and a reduction in elasticity of hybrid composites. The physical properties that were inspired by the density measurement state that the fillers used give the composites developed a lightness compared to virgin PVC.